The Role of Phase Change Materials for Lifetime Heating of Buildings in Cold Climatic Conditions (International Journal of Built Environment and Sustainability, 2020)
The study focuses on utilization of the solar insulation in buildings by means of thermal storage materials. During months of April to October, a significant part of solar gain was noticed in outer walls as well as in roof of the structure. Light weight modern construction materials have low thermal inertia so it stores less energy. The study focuses on the utilization of Phase Change Materials (PCM) for harnessing solar thermal energy for heating buildings. Various researches that show the effect of implementing PCMs in different parts of buildings like in walls, roof, windows, doors, floor etc. has been shown in the paper. The PCMs are helpful especially for those buildings which are located in cold climatic condition. Effective solutions are still required for harnessing maximum possible solar energy for heating buildings by storing heat energy by means of thermal storage materials like PCMs in hot days and to liberate it in cold night.
Keywords: PCM; Building heating; climate condition; solar in buildings; thermal storage